Subcutaneously-Administered Infliximab in the Management of Rheumatoid Arthritis: A Short Narrative Review of Current Clinical Evidence - Iannone F; Conti F; Cauli A; Farina A; Caporali R (Dove Medical Press, 2022)
Florenzo Iannone,1 Fabrizio Conti,2 Alberto Cauli,3 Alberto Farina,4 Roberto Caporali5 1Rheumatology Unit, Department of Emergency and Organ Transplantation, Università Degli Studi Di Bari Aldo Moro, Bari, Italy; 2Rheumatology Unit, Department of Clinical, Internal, Anesthetic and Cardiovascular Sciences, Sapienza Università di Roma, Rome, Italy; 3Rheumatology Unit, Department of Medical Sciences and Public Health, AOU and University of Cagliari, Monserrato, Italy; 4Medical Affairs Department, Celltrion Healthcare Italy srl, Milan, Italy; 5Department of Clinical Sciences and Community Health, Research Centre for Adult and Pediatric Rheumatic Diseases, University of Milan, Milan, ItalyCorrespondence: Florenzo Iannone, Rheumatology Unit, Department of Emergency and Organ Transplantation, Università Degli Studi Di Bari Aldo Moro, 11, Piazza Giulio Cesare, Bari (BA), 70124, Italy, Tel +39 080 5592775, Fax +39 080 5478802, Email florenzo.iannone@uniba.itAbstract: The first subcutaneous (SC) formulation of infliximab CT-P13 has been authorized for the treatment of rheumatoid arthritis (RA) in Europe in 2019. Later, in 2020, approved indications were extended also to ankylosing spondylitis, psoriatic arthritis, psoriasis, Crohn's disease (CD) and ulcerative colitis (UC). The present review provides summary of the key features of SC infliximab, with particular focus on pharmacokinetic profile, clinical development program in comparison with the intravenous (IV) formulation, and the latest evidence in the literature. We conclude that SC infliximab represents a new and promising approach in the treatment of patients with RA, offering an optimized clinical profile and a more practical option in comparison to the IV formulation. Nevertheless, SC formulation can improve the use of national health systems resources (e.g., through the time of healthcare workers not having to supervise infusions) and facilitate social distancing measures during the COVID-19 pandemic, as the patient can self-inject the medicine at home without going to the hospital. The limitations of the SC infliximab are mainly due to the limited experience of use in clinical practice and the absence of long-term drug retention data.Keywords: rheumatoid arthritis, TNF inhibitors, infliximab, subcutaneous, intravenous, SC, IV, RA